2021
DOI: 10.3390/ijgi10060380
|View full text |Cite
|
Sign up to set email alerts
|

The Use of UAV in Cadastral Mapping of the Czech Republic

Abstract: The main challenge in the renewal and updating of the Cadastre of Real Estate of the Czech Republic is to achieve maximum efficiency but to retain the required accuracy of all points in the register. The paper discusses the possibility of using UAV photogrammetry and laser scanning for cadastral mapping in the Czech Republic. Point clouds from images and laser scans together with orthoimages were derived over twelve test areas. Control and check points were measured using geodetic methods (RTK-GNSS and total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…A study by He and Li [5] illustrated that LiDAR sensor-based campaigns could also be used in land registry mapping with 5-10 cm of accuracy. A comparable investigation was conducted in the Czech Republic [6], where an experiment was also carried out to compare the results of photogrammetry-and LiDAR-based UAV measurements. The results showed that both technologies achieved the required level of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A study by He and Li [5] illustrated that LiDAR sensor-based campaigns could also be used in land registry mapping with 5-10 cm of accuracy. A comparable investigation was conducted in the Czech Republic [6], where an experiment was also carried out to compare the results of photogrammetry-and LiDAR-based UAV measurements. The results showed that both technologies achieved the required level of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Unmanned Aerial Vehicles (UAVs), due to their affordability and the ability to generate accurate photogrammetric products, are used in many areas, including land surveying (Koeva et al, 2018;Šafář et al, 2021), agriculture (Delavarpour et al, 2021;Kaivosoja et al, 2021), forestry (Dainelli et al, 2021;Pessacg et al, 2022), mining (Ge et al, 2016;Park and Choi, 2020), archeology (Campana, 2017;Fiz et al, 2022), construction (Li and Liu, 2019;Yahya et al, 2021), and road construction (Cardenal et al, 2019;Zulkipli and Tahar, 2018). Furthermore, 3D modelling of the existing infrastructure is crucial for developing increasingly popular smart cities.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing has started to be used in commercial and scientific research, such as digital mapping, monitoring of landslides and disasters, as well as monitoring and planning of agricultural land [7]. However, recently UAV solutions have been able to achieve centimetre-level accuracy, comparable to direct surveying methods, which is the reason for using drones in cadastral issues related to parcel boundaries [8][9][10][11][12][13][14][15][16][17][18]. All UAV regulations have the common goal of minimizing the risks to other airspace users and to both people and property on the ground.…”
Section: Introductionmentioning
confidence: 99%